High reliability using virtual MIMO based mesh network for maritime wireless communication - Zaidi, K.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
High-Capacity, reliable communication over sea has always been a challenge due to vast distances. Transhorizon non-line-of-sight (NLOS) communication has further reliability issues. This paper proposes a trans-horizon link based data communication with high availability in maritime wireless communication backhaul network over sea using evaporation duct. Currently long-range, high-speed backhaul communication over sea is limited to line-of-sight (LOS) distances requiring high antenna towers for microwave radio link or satellite based backhaul link which is limited in bandwidth. Using evaporation duct, present over Malaysian water in South China Sea surface to our advantage, we can achieve results for a long-range, non-line-of-sight (NLOS) maritime wireless backhaul high-speed communication link. With high reliability and capacity this could be the best alternative for long-range, high-speed maritime communication. Virtual MIMO based Mesh Network can further increase availability and capacity performance for a NLOS broadband maritime wireless communication Network. © 2016 IEEE.